Silchester revealed : the Iron Age and Roman town of Calleva - Fulford, Michael (Windgather Press, 2021)
With its apparently complete town plan, revealed by the Society of Antiquaries of London's great excavation project, 1890-1909, Silchester is one of the best known towns in Roman Britain and the Roman world more widely. Since the 1970s excavations by the author and the University of Reading on several sites including the amphitheatre, the defences, the forum basilica, the public baths, a temple and an extensive area of an entire insula, as well as surveys of the suburbs and immediate hinterland, have radically increased our knowledge of the town and its development over time from its origins to its abandonment. This research has discovered the late Iron Age oppidum and allowed us to characterise the nature of the settlement with its strong Gallic connections and widespread political and trading links across southern Britain, to Gaul and to southern Europe and the Mediterranean. 0Following a review of the evidence for the impact of the Roman conquest of A.D. 43/44, the settlement's transformation into a planned Roman city is traced, and its association with the Emperor Nero is explored. 0Modern archaeological methods have allowed us to explore a number of themes demonstrating change over time, notably the built and natural environments of the town, the diet, dress, health, leisure activities, living conditions, occupations and ritual behaviour of the inhabitants, and the role of the town as communications centre, economic hub and administrative centre of the tribal 'county' of the Atrebates.